Business Relations and Disputes in Managerial Activities - Kaxramonovna, Yusupaliyeva Dilafruz (Journal of Innovation in Education and Social Research, 2024)
This article covers the concept of business, the manager's business communication, methods of resolving conflicts in managerial activities.